Implementasi Proxy dan Snort Sebagai Gateway Antivirus - Sebayang, Andreas; Widiasari, Indrastanti Ratna (MEANS (Media Informasi Analisa dan Sistem), 2021)
Technology and internet networks are two things that are always related, because in today's era the internet has become a much-needed medium for learning, communicating, exchanging data, and even playing. With the activity of using the internet network, a problem will arise, namely network security. Network security is a very important aspect as a defense in a network, to minimize the risk of data theft and unwanted access in an internet network. The purpose of this study is to implement the control and security of internet use in an agency with minimal costs. namely using the Linux operating system Ubuntu Server 18.04, Proxy Server, and Snort. The result of the system that has been created has a function to perform caching so that it can save bandwidth and can function as filtering content to minimize unwanted things on the network. In addition, the system created is very helpful for network admins to monitor the network in real-time, even can also enforce rules to protect the network.